Investigation into the optimal fleet employment strategy with concentration on the medium range tankers (clean) east of Suez market - Chin, Gary Weng Meng. (2013)
The objective of the paper is to determine the optimal portfolio mix of for 10 Medium Range Clean Tankers for the period of 2006 to 2012Q2. This was accomplished by ascertaining the lowest cost of acquisition followed by the most profitable deployment for the vessels. The Net Present Value method was used to determine the profitable combinations and 14 combinations which had the highest positive value and distinctive risk profile were chosen. The 14 combinations were grouped together to create 1,001 portfolios.